Case of mumps orchitis after vaccination. (24th October 2013) - Kanda, Takayoshi; Mochida, Junichi; Takada, Shogo; Hori, Yutaro; Yamaguchi, Kenya; Takahashi, Satoru
Abstract: We present a case of mumps orchitis after vaccination. A 35‐year‐old man visited the emergency unit of our hospital for fever and right testicular pain on 7 January 2012. Two weeks before the visit, he underwent vaccination for mumps. After 7 days of hospitalization, the patient recovered from fever and testicular pain. Scrotal magnetic resonance imaging suggested right orchitis, and an increased level of serum mumps immunoglobulin M and immunoglobulin G indicated an initial infection of mumps virus. The peak value of immunoglobulin G showed 106 enzyme immunoassay unit 5 weeks after vaccination, which was 10‐fold higher than the ordinary rise of a vaccinated individual. This fact leads to two possibilities. One is this happened as an adverse event of vaccination, and the other is that he actually had a wild‐type infection at the same time as vaccination. There are some reports regarding adverse events of mumps vaccine; however, they might include wild‐type infection.